What Hides Behind an Unemployment Rate: Comparing Portuguese and U.S. Labor Markets - Blanchard, Olivier; Portugal, Pedro (American Economic Review, 2001)
Behind similar unemployment rates in the United States and Portugal hide two very different labor markets. Unemployment duration is three times longer in Portugal than in the United States. Symmetrically, flows of workers into unemployment are three times lower in Portugal. These lower flows come in roughly equal proportions from lower job creation and destruction, and from lower worker flows given job creation and destruction. A plausible explanation is high employment protection in Portugal. High employment protection makes economies more sclerotic; but because it affects unemployment duration and worker flows in opposite directions, the effect on unemployment is ambiguous. (JEL E2, J3, J6)